Membangun Pendidikan Berkarakter Religius dan Intelektual: Sintesis Pesantren dan Sekolah Modren - Alya Nur Affifah; Safira Laila Wulandari; Herlini Puspika Sari (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
This study is motivated by the need for an Islamic education model that can integrate religious values and intellectual intelligence amid the challenges of globalization and modernization in education. The pesantren system has excelled in shaping religious character through the instillation of values, role models, and spiritual life, while modern schools excel in developing critical thinking, scientific literacy, and adaptive skills in technology. This study aims to identify the main elements of religious and intellectual education, analyze the opportunities for synthesis between the two, and evaluate the supporting factors and obstacles in their application in the context of Indonesian education. The research method used was library research with a descriptive qualitative approach through content analysis of various scientific sources, journals, books, and educational policy documents from 2020 to 2025. The results of the study show that the synthesis of Islamic boarding schools and modern schools can be realized through the integration of curriculum, learning methods, and institutional culture that balances the spiritual and intellectual dimensions of students. This integrative education model emphasizes the importance of teachers with dual competencies, institutional management support, and adaptive curriculum policies. The implications of this study are theoretical and practical: theoretically, it enriches the concept of holistic Islamic character education, while practically, it provides direction for Islamic educational institutions to develop learning models that produce graduates who are faithful, knowledgeable, and have noble character.